The Reproducing Kernel Method for Some Variational Problems Depending on Indefinite Integrals - Fardi, Mojtaba; Ghaziani, Reza Khoshsiar; Ghasemi, Mehdi (Mathematical Modelling and Analysis, 2016)
In this paper we introduce the reproducing kernel method to solve a class of variational problems (VPs) depending on indefinite integrals. We discuss an analysis of convergence and error for the proposed method. Some test examples are presented to demonstrate the validity and applicability of method. The results of numerical examples indicate that the proposed method is computationally very simple and attractive.